Potential Criteria for Frameworks to Support the Evaluation of Innovative Medicines in Upper Middle-Income Countries—A Systematic Literature Review on Value Frameworks and Multi-Criteria Decision Analyses - Jakab, Ivett; Németh, Bertalan; Elezbawy, Baher; Karadayı, Melis Almula; Tozan, Hakan; Aydın, Sabahattin; Shen, Jie; Kaló, Zoltán (Frontiers in Pharmacology, 2020)
BACKGROUND Multicriteria Decision Analysis (MCDA), a formal decision support framework has been growing in popularity recently in the field of healthcare. MCDA can support pricing and reimbursement decisions on the macro level, which is of great importance especially in countries with more limited resources. OBJECTIVES The aim of this systematic review was to facilitate the development of future MCDA frameworks, by proposing a set of criteria focusing on the purchasing decisions of single-source innovative pharmaceuticals, in upper-middle income countries. METHODS A systematic literature review was conducted on the decision criteria included in value frameworks (VFs) or MCDA tools. Scopus, Medline, databases of universities, websites of Health Technology Assessment Agencies and other relevant organisations were included in the search. Double title-abstract screening and double full-text review were conducted, and all extracted data were double-checked. A team of researchers performed the merging and selection process of the extracted criteria. RESULTS A total of 1878 articles entered the title and abstract screening. From these, 341 were eligible for the full-text review, and 36 were included in the final data extraction phase. From these articles 394 criteria were extracted in total. After deduplication and clustering, 26 different criteria were identified. After the merging and selection process a set of 16 general criteria was proposed. CONCLUSION Based on the results of the systematic literature review, a pool of 16 criteria was selected. This can serve as a starting point for constructing MCDA frameworks in upper-middle income countries after careful adaptation to the local context.